ANALISIS PENDAPATAN USAHA PETERNAKAN AYAM BROILER KANDANG TERTUTUP (Studi Kasus di CV. Ayam Dekem Tengah Sawah) (Analysis of Income Closed Cage Broiler Chicken Farming Business (Case Study at CV. Ayam Dekem Tengah Sawah) - Wachid, Sinta Nur; Yuliati, Nuriah; Laily, Dona Wahyuning (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
Jombang Regency is one of the areas that develops broiler chicken farming centers. Jombang Regency, which consists of 20 sub-districts, almost entirely manages and develops poultry farming. One of the broiler chicken farms is located in Peterongan sub-districts, Jombang Regency, namely CV. Ayam Dekem Tengah Sawah. The problems and challenges that often become the main topic in broiler chicken farming are limited resources, including land and feed. The objective of this research is to examine the costs, income, and business feasibility of broiler chicken farming at CV. Ayam Dekem Tengah Sawah. This research employs cost analysis and business feasibility analysis methods. The findings indicate that CV. Ayam Dekem Tengah Sawah’s revenue in one periode amounts to Rp. 2.30.130.370, with an income of Rp. 1.963.147.124. The R/C ratio is 1,17 (>1), and the ROI is 8%. Therefore, it can be inferred that the broiler chicken farming business at CV. Ayam Dekem Tengah Sawah is profitable and worthy of development.Keywords: Broiler Chicken, Income, Business Feasibility.